CuH-Catalyzed Regioselective Intramolecular Hydroamination for the Synthesis of Alkyl-Substituted Chiral Aziridines - Wang, Haoxuan (J Am Chem Soc, 2017)
This report details a general and enantioselective means for the synthesis of alkyl-substituted aziridines. This protocol offers a direct route for the synthesis of alkyl-substituted chiral aziridines from achiral starting materials. Readily accessed allylic hydroxylamine esters undergo copper hydride-catalyzed intramolecular hydroamination with a high degree of regio- and enantio-control to afford the aziridine products in good to excellent yield in highly enantioenriched form. The utility of the products derived from this method is further demonstrated through the derivatization of chiral aziridine products to a diverse array of functionalized enantioenriched amines.